Welfare Dominance: An Application to Commodity Taxation - Yitzhaki, Shlomo; Slemrod, Joel (American Economic Review, 1991)
In this paper, we propose a method to identify commodity-tax changes that will be favored by all individuals who can agree on certain weak assumptions with regard to the social-welfare function. The method is based on an extension of the criterion of second-degree stochastic dominance and is illustrated using data from Israel.